2017
DOI: 10.3389/fendo.2017.00299
|View full text |Cite
|
Sign up to set email alerts
|

A Testis-Specific Long Non-Coding RNA, lncRNA-Tcam1, Regulates Immune-Related Genes in Mouse Male Germ Cells

Abstract: Spermatogenesis is precisely controlled by hormones from the hypothalamus–pituitary–gonadal axis and testis-specific genes, but the regulatory mechanism is not fully understood. Recently, a large number of long non-coding RNAs (lncRNAs) are found to be transcribed at each stage of meiosis of male germ cells, and their functions in spermatogenesis have yet to be fully investigated. lncRNA-testicular cell adhesion molecule 1 (lncRNA-Tcam1) is a nuclear lncRNA which is specifically expressed in mouse male germ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 74 publications
0
28
1
Order By: Relevance
“…Total RNA was extracted from isolated follicles, purified, and treated with TURBO DNase as previously described (Matsubara et al, 2017). A total of 500 ng or 150 ng of quality-verified RNA from sieved follicles or further purified follicles, respectively, was subjected to RNA-seq analysis using a HiSeq1500 instrument (Illumina, San Diego, CA) in the rapid mode, as previously described (Kawada et al, 2017; Kurihara et al, 2017). The resultant reads were aligned to the Ciona cDNA library, which was downloaded from the ghost database (http://ghost.zool.kyoto-u.ac.jp/cgi-bin/gb2/gbrowse/kh/).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from isolated follicles, purified, and treated with TURBO DNase as previously described (Matsubara et al, 2017). A total of 500 ng or 150 ng of quality-verified RNA from sieved follicles or further purified follicles, respectively, was subjected to RNA-seq analysis using a HiSeq1500 instrument (Illumina, San Diego, CA) in the rapid mode, as previously described (Kawada et al, 2017; Kurihara et al, 2017). The resultant reads were aligned to the Ciona cDNA library, which was downloaded from the ghost database (http://ghost.zool.kyoto-u.ac.jp/cgi-bin/gb2/gbrowse/kh/).…”
Section: Methodsmentioning
confidence: 99%
“…It is exclusively expressed in mouse male germ cells and is assumed to play a crucial role in meiosis. In a recent report, it was found that lncRNA-Tcam1 regulates immune related genes in mouse germ cells [ 132 ]. The induction of lncRNA-tcam1 transcription using the tet-off system in GC-2 cells upregulated six genes, Trim30a, Ifit3, Tgtp2, Ifi47, Oas1g, and Gbp3.…”
Section: Introductionmentioning
confidence: 99%
“…Tslrn1 is highly expressed in mouse primary spermatocytes, and mice with its knockout showed a significant reduction in spermatozoa [20]. Our group identified lncRNA-Tcam1 that is expressed at a high level in spermatocytes and suggested that it regulates immune-related genes for immune response during meiosis [88]. Downregulation of mrhl RNA is required for activation of Wnt signaling and the entry of spermatogonia into meiosis [89].…”
Section: Discussionmentioning
confidence: 99%